Comments on the Morphology of Basal Paravian Shoulder Girdle: New Data Based on Unenlagiid Theropods and Paleognath Birds - Novas, Fernando E.; Motta, Matías J.; Agnolín, Federico L.; Rozadilla, Sebastián; Lo Coco, Gastón E.; Brissón Egli, Federico (Frontiers in Earth Science, 2021)
In 1976 John Ostrom published an enlightening paper about the anatomical transformations in the shoulder girdle and forelimb elements along the origin of birds. Most of his ideas were based on comparing Archaeopteryx lithographica with the extant New World vulture Cathartes aura. Ostrom offered innovative ideas about range of movements and function of wing elements in the basal bird Archaeopteryx. Further, he explored anatomical transformations that may have occurred at early stages of the evolution of flight and established several hypothetical steps towards the acquisition of flapping flight in modern birds. Since then, however, our understanding of paravian diversity and anatomy has increased dramatically. Based on novel information derived from recent experiments, and currently available anatomical evidence of basal paravians, the present paper aims to review some important topics on pectoral girdle anatomy related to flight origins. Further, a brief analysis of pectoral girdle osteology and myology of the extant paleognath Rhea americana is also included with the aim to test whether Ostrom’s ideas still remain valid under this new context and based on available phylogenetic and anatomical frameworks.